The Metaphysics of Experience A Companion to Whitehead's Process and Reality - Kraus, Elizabeth (Fordham University Press, 2019)
The Metaphysics of Experience styles itself as "a Sherpa guide to Process and Reality, whose function is to assist the serious reader in grasping the meaning of the text and to prevent falls into misinterpretation." Although originally published in 1925, Process and Reality has perhaps even more relevance to the contemporary scene in physics, biology, psychology, and the social sciences than it had in the mid-twenties. Hence its internal difficulty, its quasi-inaccessibility, is all the more tragic, since, unlike most metaphysical endeavors, it is capable of interpreting and unifying theories in the above sciences in terms of an organic world view, instead of selecting one theory as the paradigm and reducing all others to it. Because Alfred North Whitehead is so crucial to modern philosophy, The Metaphysics of Experience plays an important role in making Process and Reality accessible to a wider readership.